PERSEPSI AKUNTAN: ACCOUNTING CYCLE BERBASIS AKRUAL DAN KUALITAS PELAPORAN KEUANGAN - Yonatan Alvin Stefan; Rossiana Kharisma Ramadhani (Jurnal Ilmu Akuntansi, 2026)
The purpose of this study is to examine how accountants' opinions about the accrual-based accounting cycle's implementation affect the caliber of financial reporting. This study focuses on the ways that accountants' professional skill, cognitive comprehension, and dedication to accounting rules enhance the caliber of financial reporting. With a sample size of 150 accountants, the study used a quantitative methodology with a causal research design. The connection between independent and dependent variables was examined using SEM-PLS. The findings demonstrate that the quality of financial reporting is significantly improved by the use of the accrual-based accounting cycle. The Information Usefulness Theory, which contends that financial data must be trustworthy and pertinent in order to aid in economic decision-making, is supported by this study. Thus, enhancing accountants' knowledge, expertise, and dedication to accounting standards is essential to raising the caliber and legitimacy of financial reporting procedures.